Environment Content-Based Teaching Material Construction for Social Studies - Yuniar, Listya Eka; Pramono, Suwito Eko; Priyanto, Agustinus Sugeng (Universitas Negeri Semarang, 2019)
Environment content-based teaching material construction for social studies has become the prototype of the environment content-based social studies learning module for class VII SMPN students in Cirebon. Based on how to develop the construction of the social studies teaching material in accordance with the social studies learning nature so the positive impact on social studies learning activities. This research is R&D development with Borg and model Gall. The purpose of research in this research is to develop the construction of an environmental-based social studies teaching material that suits the types of social studies learning so that it positively affects the learning activities of social studies. The construction of the environmental-based social studies teaching materials in Cirebon, covering several phases including intelligence, schematic, assimilation and accommodation, equalization, and interiorization. The final result of this study is the development of an environmental-based social studies learning module with emphasis on students cognitive structure through the process of the asimilasi and the accommodation supported by direct visits to the Cirebon Kasepuhan. All experiences involve two similar processes such as introduction, or knowing, in connection with the assimilation process, and accommodation that results in a cognitive structure modification. These modifications can be shown as a learning process. Students show the environment-based social studies modules can also be a solution to improve quality in social studies learning